(untitled) (Confluenţe Bibliologice, 2022)
The article discusses the role of motivation and professional satisfaction of the university librarian. The motivation approaches the way of determining the means by which the members of an organization, respectively, the librarians, can be stimulated to effectively contribute to the achievement of the objectives, taking into account the needs of each and the personal characteristics.